A Comparative Study of the Effects of Aerobic and Resistance Training on Physical and Cognitive Health in Older Adults - Alireza Babaei Mazreno; Farzaneh Taghian (Elderly Health Journal)
As the global population ages, maintaining health and functionality in older adults has become a key public health priority. Exercise is widely recognized as a powerful intervention to enhance physical and mental health, reduce the risk of chronic diseases, and improve the quality of life in older adults. Among the various types of physical activity, aerobic and resistance exercises are two of the most frequently recommended for elderly populations. This article provides a detailed comparison of these two forms of exercise, examining their effects on cardiovascular health, musculoskeletal integrity, cognitive function, metabolic health, psychological well-being, and overall quality of life in older adults.